Valence electron structures and properties of Ni-based corrosion resistant alloy - 杨瑞成 舒俊 陈奎 王凯旋 (Transactions of Nonferrous Metals Society of China, 2007)
The corrosion resistance and mechanical properties were tested and compared for the newly synthesized as-cast, as-solution Ni-Cr-Mo-Cu corrosion resistant alloys and 1Cr18Ni9Ti austenitic stainless steel. Their valence electron structural units were constructed, and the relative parameters were calculated by means of the Empirical Electron theory of Solids and Molecules （EET）. The results show that, during alloy elements Cr, Mo and Cu entering Ni-matrix, the bonding strength nA and bonding energy EA of the strongest bond of the alloy are greatly increased, causing the stronger solid solution strengthening effects （about 30% increase in σb）. Also, as reinforcement of the main bond network and the improvement of stability of the alloy system due to the solution of these alloying elements in γ-Ni, the ionization of metal atoms in corrosion solution and the flow of electrons from anode to cathode would all be impeded during electro-chemical corrosion processes, which leads to the excellent corrosion resistant ability of the present Ni-Cr-Mo-Cu alloy （about 2-3 orders of magnitude as high as 1Cr18Ni9Ti austenitic stainless steel） in several highly aggressive solutions.